A School-based Management and Supervision Model in EFL Schools - Nurhuda. H Nurhuda. H (Universitas Lancang Kuning, 2014)
This article offers a school-based reflective management model in EFL schools that centers on reflective practice for EFL teachers and administrators drawing on four bodies of literature (reflective thinking, supervision, teacher inquiry in EFL context and organizational learning). This study introduce